2006
DOI: 10.1038/sj.onc.1209976
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 is a novel regulator of ErbB1 receptor trafficking

Abstract: ErbB receptors are key regulators of cell survival and growth in normal and transformed tissues. The oncogenic glycoprotein MUC1 is a binding partner and substrate for erbB1 and MUC1 expression can potentiate erbBdependent signal transduction. After receptor activation, erbB1 is typically downregulated via an endocytic pathway that results in receptor degradation or recycling. We report here that MUC1 expression inhibits the degradation of ligand-activated erbB1. Through the use of both RNAi-mediated knock dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 37 publications
(41 reference statements)
7
110
1
Order By: Relevance
“…Interestingly, EGFR is also aberrantly expressed in pancreatic cancer from intraepithelial neoplasia lesions to PDAC and exhibits membrane and cytoplasmic staining (Ozaki et al, 2009). Previous reports demonstrated that MUC1 physically interacts with EGFR at the cell membrane, promotes its endocytosis and recycling, and inhibits its degradation (Li et al, 2001;Schroeder et al, 2001;Pochampalli et al, 2007;Ramasamy et al, 2007). These data raise evidence for a connection between MUC1 and EGFR trafficking, and downstream signalling pathways.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, EGFR is also aberrantly expressed in pancreatic cancer from intraepithelial neoplasia lesions to PDAC and exhibits membrane and cytoplasmic staining (Ozaki et al, 2009). Previous reports demonstrated that MUC1 physically interacts with EGFR at the cell membrane, promotes its endocytosis and recycling, and inhibits its degradation (Li et al, 2001;Schroeder et al, 2001;Pochampalli et al, 2007;Ramasamy et al, 2007). These data raise evidence for a connection between MUC1 and EGFR trafficking, and downstream signalling pathways.…”
Section: Introductionmentioning
confidence: 69%
“…In contrast, in epithelial cancers MUC1 is often overexpressed and delocalized to the whole cell membrane and/or the cytoplasm thus allowing an interaction with EGFR. These interactions modulated the EGFR pathways at different levels, that is, inhibition of EGFR degradation, stimulation of EGFR recycling to the cell membrane and promotion of EGFR localization in the nucleus (Pochampalli et al, 2007;Bitler et al, 2010). Reciprocally, EGF-activated EGFR phosphorylates MUC1 CT on tyrosine, and facilitates its interaction with b-catenin (Singh and Hollingsworth, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 interacts with EGFR, and activated EGFR tyrosine phosphorylates the MUC1 cytoplasmic domain at a -YEKV-motif that upon phosphorylation serves as a docking site for the c-Src SH2 domain (67). MUC1 also protects against EGFR ubiquitination, thereby promoting its postinternalization plasma membrane recycling and signaling (68). The net effect of NEU1-mediated desialylation on the EGFR-MUC1 receptor signaling complex is likely complicated and incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…3) (Horne et al, 2005;Singh et al, 2010, Bastu et al, 2015. Moreover, paracrine signals from embryos appear to regulate MUC1 to alter local epithelial phenotypes, possibly via growth factors, including insulin-like growth factor (IGF) (Fluhr et al, 2008) and heparin-binding epidermal growth factor (HB-EGF) (Paria et al, 2001;Pochampalli et al, 2007;Lim and Dey, 2009). MUC1 therefore appears to be a key player in regulating endometrial receptivity for implantation and should be the focus of continued research.…”
Section: Osteopontinmentioning
confidence: 99%